Consistent patterns of Antarctic ice sheet interannual variations from ENVISAT radar altimetry and GRACE satellite gravimetry - Horwath, M.; Legresy, Benoit; Rémy, Frédérique; Blarel, Fabien; Lemoine, Jean-Michel (Geophysical Journal International, 2012)
International audience